Quo Vadis semiempirical MO-theory? - Clark, Timothy (Journal of Molecular Structure-Theochem, 2000)
Some of the essential features, strengths and weaknesses of semiempirical MO theory are discussed and suggestions made as to the role of this type of theory in the future and likely development directions. The impact of theories with an empirical component on computational chemistry is discussed. (C) 2000 Elsevier Science B.V. AU rights reserved.
Keywords: semiempirical MO-theory; linear scaling; QM/MM; polarizability; NDDO; MNDO; AM1; PM3